Family caregivers: what do they need? An integrative review - Carla Sílvia Fernandes; Margareth Angelo
Abstract OBJECTIVE Aimed to identify the main needs expressed by family caregivers in caring for adependent person. METHOD An integrative review of the literature in the period between 2010 and 2015 using specific search engine tools in the EBSCO and SCOPUSdatabases. RESULTS 11 articles were selected, and the analysis of the scientific evidence obtained allowed for organizing the results into five thematic areas:transition into care, being responsible for everything, the importance of support, access to formal support, communication and informationprocesses. CONCLUSION The results showed that caregivers have many needs in different areas, which should be addressed in nursing interventions.